2011
DOI: 10.17221/3266-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of marker-based selection for Fusarium head blight resistance in spring wheat

Abstract: Abstract:The effect of selection for two donor-QTL from Fusarium head blight (FHB) resistant spring wheat variety Sumai 3 on the reduction of deoxynivalenol (DON) content and FHB index was evaluated in field trials over two years (2008, 2009) following artificial inoculation with Fusarium culmorum. This study was conducted on populations of recombinant inbred lines derived from two crosses, Sumai 3/Swedget and Sumai 3/SG-S 191-01. DON content and FHB index were significantly reduced in both crosses in the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The Asian spring wheat resistance QTL Fbh1 , Fhb2 , Fhb5/Qfhs‐ifa‐5A and QFhs.nau‐2DL have proven to be effective in spring wheat and winter wheat as well. Chrpova et al (), Salameh et al (), Suzuki et al () and von der Ohe et al () validated effectiveness of Fhb1 and Fhb5 / Qfhs.ifa‐5A in diverse genetic backgrounds. Studies demonstrated that in most cases already the presence of a single QTL significantly improved resistance; however, the presence of both Fhb1 and Fhb5 was more efficient and stable in increasing resistance compared to single QTL carriers.…”
Section: The Role Of Morphological Traits As Passive Fhb Resistance Fmentioning
confidence: 98%
“…The Asian spring wheat resistance QTL Fbh1 , Fhb2 , Fhb5/Qfhs‐ifa‐5A and QFhs.nau‐2DL have proven to be effective in spring wheat and winter wheat as well. Chrpova et al (), Salameh et al (), Suzuki et al () and von der Ohe et al () validated effectiveness of Fhb1 and Fhb5 / Qfhs.ifa‐5A in diverse genetic backgrounds. Studies demonstrated that in most cases already the presence of a single QTL significantly improved resistance; however, the presence of both Fhb1 and Fhb5 was more efficient and stable in increasing resistance compared to single QTL carriers.…”
Section: The Role Of Morphological Traits As Passive Fhb Resistance Fmentioning
confidence: 98%
“…The parents of Sumai 3 (Funo from Italy and Taiwanxiaomai from China) were moderate resistant genotypes [44], therefore Fhb1 alone cannot secure high resistance) as supposed in many early papers having 3BS (fhb1) QTL [9]. Chrpova et al [11] reported no significant difference between 3BS and no QTL plants (this could be genotype dependent), but the 3BS+5AS plants showed much better resistance.…”
Section: Type I and Type Ii Resistance To Infection And Spreadingmentioning
confidence: 99%
“…However, only a few QTL have been validated across studies and solely Fhb1 (Cuthbert et al 2006 ), Fhb2 (Cuthbert et al 2007 ), Fhb4 (Xue et al 2010 ), Fhb5 (Xue et al 2011 ), and Qfhs.ndsu - 3AS (Zhu et al 2016 ) have been subjected to fine-mapping to identify tightly linked markers. Qfhs.ifa - 5A (Buerstmayr et al 2002 , 2003 ) is among the most frequently studied resistance QTL and was validated either individually or in combination with other QTL (Bokore et al 2017 ; Chen et al 2006 ; Chrpova et al 2011 ; Kang et al 2011 ; McCartney et al 2007 ; Salameh et al 2011 ; Suzuki et al 2012 ; Tamburic-Ilincic 2012 ; von der Ohe et al 2010 ). Qfhs.ifa - 5A mapped across the centromere of chromosome 5A within a 1.6 cM QTL support interval flanked by the SSR markers barc186 and wmc805 (Buerstmayr et al 2003 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%